Flexible Communication of Agents based on FIPA-ACL - Bagherzadeh, Jamshid; Arun-Kumar, S. (Electronic notes in theoretical computer science, 2006)
Communication in multi-agent systems is an important subject of the current research. In this paper, the syntax and semantics of a multi-agent programming language, called ECCS, are defined. We focus specially on the communication of agents. The main contribution of this paper is a new and flexible way of communication of agents. We finally work out a well known protocol as an example.